Caracterização pedogeoquímica das formações superficiais representativas da superfície geomorfológica de Erval Grande – planalto das araucárias - Oliveira, Daniella Rosa Marques De (2020)
This dissertation aimed at the pedogeochemical characterization of the representative superficial formations of Erval Grande Geomorphologic Surface, inserted in the Araucarias Highland. In order to achieve the main objective, a field research was carried out for the macromorphological individualization of the materials and samples collection for analysis. At the lab the following analyses were determined: granulometric, macronutrient chemistry, sulfuric attack of the clay fraction, determination of free, total and amorphous iron, total quantitative chemical analysis by X-ray fluorescence spectrometry - merged pellet and pressed powder, mineralogy by X-ray diffraction (XRD) and micromorphology. The section of superficial formations is located in a fissure at state highway in the north of Rio Grande do Sul, Alto Uruguai Sector. Altogether 970 cm of vertical extension material exposed in 08 volumes were individualized, being that the first 05 corresponding to the solum. The others to the alterite, the volumes 06 and 07 with characteristics of aloterite and the volume 08, isolterite. The solum includes the horizons: Ap, AB, BA, Bw, BC. The alterite is divided into Cg1, Cg2 and Cg3. The macromorphological characteristics association of the macronutrient indices allows to individualize the horizon B as Red Dystrophic Aluminum Latosol. This characteristic is confirmed by the Ki and Kr indices, which suggest that the material is well weathered, with kaolinitic characteristics. The levels of free, total and amorphous iron indicate that the iron is still being released. The samples semiquantitative analysis of the rock served to determine the type of specific lithology of the geomorphologic surface of Erval Grande – RS. The TAS diagram was used for the classification of volcanic rocks of the area, being that the data obtained in the studied section indicate the predominance of Andesite. The total chemistry of the ten main oxides of the materials of the profile studied, as of the molecular relationship of Ki and Kr, fit in the type of coverage of fersialitic. The mineralogical analysis of the clay fraction revealed minerals of the Philosilicate family: kaolinite, vermiculite hydroxy between layers and haloisite. Of the Silicates: cristobalite, quartz, chlorite and tridymite. And from of Oxides and Hydroxides classes, the gibbsite, anathelite, goethite and hematite. From the identified minerals, kaolinite and gibsite reflect conditions of pedogeochemical formations of the monosialitization kind. In micromorphology analysis, it made sure that the ferruginous crust is being formed from the migration of iron hydroxides released from the solum’s materials.